The Japanese Corporate Family: The Marital Gender Contract Facing New Challenges. (May 2019) - Goldstein-Gidoni, Ofra
The analytical prism of gender contract is used in this article as a means to conceptualize the cultural construction of the idea of the heteronormative "ordinary" Japanese family, a construct that gained hegemonic dominance over the course of Japan's stable prosperous postwar period (1960s-1980s); and from there, for examining the strength of this normative "contract" against post-bubble economic and social challenges. To further challenge the potential changes in the corporate gender contract, —particularly against the corporate culture—the study purposely sampled the second group of male and female interviewees, who were related to the so-called ikumen movement, which calls for greater involvement of men in family life and a better work–life balance. These men and women were not only from younger age cohorts compared to the first group of women and men. They also mostly resided in dual-income households, unlike the first group whose households were mainly based on a male breadwinner.